Apre(e)nder a cidade, o urbano e o cosmos: interseções entre espaço e educação - Marcela Rosenburg Figueiredo (2021)
The research investigates the existing and possible intersections between space and education. For this purpose, multiple educational, cultural and artistic experiences are taken into account. By bringing space into discussion, such experiences enable a debate about the learning processes that emerge from them, unfolding a reflection on the role and the (im)possibilities presented by architectural and urban practices in relation to this type of pedagogy. Finally, as the research proposes to think about learning in space, from space and about space, it resumes the discussion of the urban as a way to articulate the (re)politicization of the everyday life. By approaching current issues such as the planetary scale of urbanization, the Anthropocene and the critique on coloniality, this research is in an attempt to understand what could constitute a pedagogy that goes beyond the space of the city and the urban, as it expands itself towards the cosmos.